2015
DOI: 10.1021/acs.langmuir.5b02458
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage to Biomimetic Membrane Systems: In Situ Fe(II)/Ascorbate Initiated Oxidation and Incorporation of Synthetic Oxidized Phospholipids

Abstract: Damage to cellular membranes from oxidative stress has been implicated in aging related diseases. We report the effects of oxidative damage on the structure and properties of biomimetic phospholipid membrane systems. Two oxidation methods were used, in situ oxidation initiated using Fe(II) and ascorbate, and the incorporation of a synthetic "oxidized" phospholipid, PoxnoPC, into biomimetic membranes. The biomimetic systems employed included multibilayer stacks, tethered bilayers, and phospholipid monolayers st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Typical examples of model membrane systems are Langmuir monolayers, vesicles or liposomes and solid supported bilayers (Figure 4 ). All of these systems offer advantages and disadvantages for the study of peptide-membrane interactions (Knobloch J. J et al, 2015 ).…”
Section: Model Lipid Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical examples of model membrane systems are Langmuir monolayers, vesicles or liposomes and solid supported bilayers (Figure 4 ). All of these systems offer advantages and disadvantages for the study of peptide-membrane interactions (Knobloch J. J et al, 2015 ).…”
Section: Model Lipid Membranesmentioning
confidence: 99%
“…The partition coefficient or affinity constant does not contain, in principle, information about the solute location (i.e., the peptide) in the membrane, which can be either adsorbed at the membrane interface or internalized at different depth into the lipid bilayer. This structural information can be obtained by using other spectroscopic methodologies such as differential fluorescence quenching (Nicoli et al, 2010 ; Knobloch J. J et al, 2015 ; Li et al, 2015 ). In this technique quencher molecules that take different positions in the membrane are used, as 5NS and 16NS Stearic acid molecules derivatized with doxyl (quencher) groups either at carbon 5 or 16, respectively.…”
Section: Amps Membrane Interactionmentioning
confidence: 99%
“…The reason for this decrease in mitochondrial membrane potential during aging is unknown but the enhancement of ROS formation, which is likely to modify mitochondrial membrane components and to promote mitochondrial uncoupling, is probably involved. Indeed, oxidative stress was shown to alter the fluidity and the permeability of membranes (Knobloch, Nelson, Köper, James, & McGillivray, 2015; Runas & Malmstadt, 2015). Whether the decrease in membrane potential is the cause or the result of the activation of mPTP opening is not clearly established.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%
“…The acyl chain reversal increases the area per lipid, leads to bilayer thinning, and decreases lipid chain conformational order, thus promoting water permeability and membrane deformation. The effects of oxidized lipids on the structure and permeation properties of lipid bilayers have been studied by simulations (10,51,68,75,93,101) and experiments (39,87) quite extensively. A recent computational study demonstrated how the polar groups of oxidized lipids perturb the bilayer, induce formation of pores and other membrane defects, and also induce micellation (10).…”
Section: Polyunsaturated Fatty Acids Involved In Stress Response Undementioning
confidence: 99%